Original Article Comparison of three difficult endotracheal intubation predictors in obese individuals in an Indian population: Predictors of difficult intubation in Obese Indians (Bombay Hospital Journal, 2024)
Abstract: Context: Unanticipated difficult intubation is a challenge that no single bedside screening test can accurately predict. Independent indices or single anthropometric measurements have demonstrated lower reliability in patients with increased Body mass index (BMI). Using two or three related independent indices is therefore preferred.  Aim:To assess applicability of three bedside measurements, the modified Mallampati Classification (MMPC), Neck circumference and Thyromental distance ratio (NC/TM) and Neck Circumference minus acromio-acromion distance (NEMA) in obese subset of Indian population. Design:  Prospective observational study Methods and Material:One twenty adults with BMI > 29 undergoing general anesthesia were enrolled after consenting.  Pre-operative measurements and intubation details were recorded. Difficult intubation was determined using the intubation difficulty scale (IDS≥5 termed difficult). The NC/TM ratio, NEMA, MMPC were compared with respect to sensitivity, specificity, positive, negative predictive value with receiver operating characteristics (ROC) curve and logistic regression.Statistical analysis used:  SPSS software version 25 ResultsIncidence of difficult intubation was 12.5%. By binary univariate logistic regression, NC/TM independently predicted difficult intubation in obese {p = 0.00 and exponential B 29.173(95% CI of 5.862 to 145.185)}. NC/TM showed the highest sensitivity, negative predictive value, and largest area under the curve.. Mean NC/TM was 4.71(SD ± 0.44) and mean NEMA was 0.83(SD ± 2.7) ConclusionThe NC/TM ≥5 with its good sensitivity, specificity, negative and positive predictive values, appears an independently useful, simple bedside test predicting difficult intubation in obese Indian population and superior to MMPC and NEMA.
Keywords: predictors; laryngoscopy; obesity; airway risk assessment; difficult endotracheal intubation